Olfactory Receptors as Biomarkers in Human Breast Carcinoma Tissues - Lea Weber (Frontiers in Oncology, 2018)
Olfactory receptors (ORs) are known to be expressed in a variety of human tissues and act on different physiological processes, such as cell migration, proliferation, or secretion and have been found to function as biomarkers for carcinoma tissues of prostate, lung, and small intestine. In this study, we analyzed the OR expression profiles of several different carcinoma tissues, with a focus on breast cancer. The expression of OR2B6 was detectable in breast carcinoma tissues; here, transcripts of OR2B6 were detected in 73% of all breast carcinoma cell lines and in over 80% of all of the breast carcinoma tissues analyzed. Interestingly, there was no expression of OR2B6 observed in healthy tissues. Immunohistochemical staining of OR2B6 in breast carcinoma tissues revealed a distinct staining pattern of carcinoma cells. Furthermore, we detected a fusion transcript containing part of the coding exon of OR2B6 as a part of a splice variant of the histone HIST1H2BO transcript. In addition, in cancer tissues and cell lines derived from lung, pancreas, and brain, OR expression patterns were compared to that of corresponding healthy tissues. The number of ORs detected in lung carcinoma tissues was significantly reduced in comparison to the surrounding healthy tissues. In pancreatic carcinoma tissues, OR4C6 was considerably more highly expressed in comparison to the respective healthy tissues. We detected OR2B6 as a potential biomarker for breast carcinoma tissues.